(untitled) - Drengubiak, Ján (Romanica Olomucensia, 2013)
The article presents a critical overview of the works of Richard Millet who started writing in 1983. Since then, Millet has written a few dozens of books that can be sorted according to several criteria. The subject matter of this paper is to grasp the evolution of the central themes of the author's writings.
Keywords: Richard Millet; author; French contemporary fiction; autobiography.